2022
DOI: 10.1186/s40337-022-00605-x
|View full text |Cite
|
Sign up to set email alerts
|

First, do no harm: the proposed definition of “terminal anorexia” is fraught with danger for vulnerable individuals

Abstract: A recent article in the Journal of Eating Disorders (10:23, 2022) proposed criteria for “terminal anorexia” with a cited goal of improving access to end-of-life care (Gaudiani et al. in J Eat Disord 10(1):23, 2022). The authors presented three cases in which patients received end-of-life care, including the prescription of medical assistance in dying (MAID), also known as physician-assisted suicide (PAS). The proposed criteria lack the evidence base for adoption and do not acknowledge the compelling evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Based on these two articles [ 5 , 6 ] and anonymous review comments, we identified critical responses or concerns (presented in italics) that can be grouped into five categories, each of which we address separately. Our analysis reveals that the critiques of our presentations all rest on substantially questionable premises.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these two articles [ 5 , 6 ] and anonymous review comments, we identified critical responses or concerns (presented in italics) that can be grouped into five categories, each of which we address separately. Our analysis reveals that the critiques of our presentations all rest on substantially questionable premises.…”
Section: Resultsmentioning
confidence: 99%
“…Since publication of our article, to identify specific concerns about our proposals, a supplemental literature review was conducted through PubMed to collect relevant response articles in the subsequent literature. Two titles met inclusion criteria: Guarda et al [ 5 ] and Riddle et al [ 6 ]. Additional concerns were derived from comments provided by anonymous reviewers in response to our submitted manuscripts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another new mental health issue for this population involves the term "terminal AN. " While criteria for "terminal AN" have recently been proposed and may be cited in the ED as justification for refusal of life-saving treatment, it is crucial to recognize that at this time, there are no evidence-based criteria to support a diagnosis of "terminal AN" [13][14][15]. Data suggest that recovery can occur even after decades of this illness [16].…”
Section: Emergency Psychiatric Issuesmentioning
confidence: 99%
“…Since that time, five papers have been published cautioning about the use of the term “terminal AN” (Guarda et al, 2022; Riddle et al, 2022; Mack & Stanton, 2022; Elwyn, 2023; Downs et al, 2023), and Drs Yager and Gaudiani along with another colleague have published a response (2022). This is an important and unavoidably controversial topic requiring careful consideration and debate.…”
Section: Introductionmentioning
confidence: 99%